2012
DOI: 10.1007/s00127-012-0593-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of adequate depression treatment among Medicaid-enrolled youth

Abstract: While the majority of youth appear to be receiving minimally adequate acute care for depression, a substantial number are not. Given current child mental health workforce constraints, efforts to substantially improve the provision of adequate care to depressed youth are likely to require both quality improvement and system redesign efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…Notably, the relative size of the disparity was larger for minimally adequate pharmacotherapy than for minimally adequate psychotherapy. This pattern of findings is similar to prior research, 17 which compared adequate treatment between non-white and white Medicaid-enrolled youth in an urban county. The residual disparities can be explained by unmeasured racial/ethnic differences in attitudinal barriers, such as stigma concerning depression and its treatment, or unmeasured systems-level barriers, such as patient-provider language concordance or provider cultural competency.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Notably, the relative size of the disparity was larger for minimally adequate pharmacotherapy than for minimally adequate psychotherapy. This pattern of findings is similar to prior research, 17 which compared adequate treatment between non-white and white Medicaid-enrolled youth in an urban county. The residual disparities can be explained by unmeasured racial/ethnic differences in attitudinal barriers, such as stigma concerning depression and its treatment, or unmeasured systems-level barriers, such as patient-provider language concordance or provider cultural competency.…”
Section: Discussionsupporting
confidence: 88%
“…AACAP guidelines recommend that 4 to 6 weeks of supportive therapy (in uncomplicated or brief cases of depression) or 6 to 8 weeks of other types of psychotherapy (eg, cognitive behavioral therapy) are needed to assess responsiveness to treatment. 8 Consistent with the work of Stein et al, 17 we used a 4-visit threshold for the main analyses to capture the lower bound of this recommendation (assuming 1 visit per week over 4 weeks). We also created an alternative measure using an 8-visit threshold in supplemental analyses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have found that Medicaid recipients are at higher risk for major mental health diagnoses and substance use disorders when compared to national averages (Adelmann, 2003) and that youth with Medicaid are more likely to meet criteria for a Severe Emotional Disturbance (SED) than youth with private insurance (Mark & Buck, 2006). Additionally, many children with public insurance do not receive adequate access to quality care (Semansky, Koyanagi, & Huffine, 2004;Stein et al, 2013). For suicidal youth, barriers to quality care may prevent them from receiving treatment that adequately addresses their mental health needs.…”
Section: Public Insurance and Suicide Risk Among Adolescentsmentioning
confidence: 99%